Comparison of prevalence of metabolic disorders of urban and rural adults of Punjab, India - Poonam Bakhetia; Kiran Bains; Sukhinder Cheema (Wolters Kluwer Medknow Publications, 2023)
A study was conducted to determine the prevalence of metabolic syndrome (MetS) in urban and rural areas of Ludhiana district, Punjab. A total of 1000 subjects aged 25-65 years were selected for screening. The study found that both urban and rural areas had an average body mass index above 23.0 kg/m2, with rural populations having higher waist circumference, hip circumference, and waist-hip ratios. Abdominal obesity was more prevalent in women in both areas. Rural men and women had higher fasting blood glucose and systolic blood pressure/diastolic blood pressure levels. MetS prevalence in urban areas is lower among men (7%) and women (10%) compared to rural areas (34% and 26%). The timely detection of metabolic disorder risk factors and intervention can effectively address MetS in the Indian population, thereby improving the country's health statistics.